Amoebiasis: a 10 year retrospective study at the University Hospital, Kuala Lumpur - Jamaiah, I.; Shekhar, K.C. (Malaysian Medical Association, 1999)
A hospital based retrospective study of amoebiasis was carried out for a ten-year period at the University Hospital, Kuala Lumpur. Of the 51 cases traced, 30 (59) had amoebic dysentery, 20 (39) were amoebic liver abscess (ALA) and one patient had both conditions. Entameoba histolytica trophozoites were identified in 13 (43) of the amoebic dysenteric stools and 9 (30) from biopsy. Of the 20 (39) ALA cases, only one showed parasites in the stool and biopsy. Majority of the patients with dysentery were Malays while Chinese comprised 40 with ALA. Males predominated overall with a male female ratio of 3:1, while for ALA it was 9:1. Most of ALA were single (71.4) and were localised in the right lobe. The majority of the patients were unemployed. Eighty three percent (83) of the patients presented with diarrhoea or dysentery followed by abdominal pain while those with ALA had fever, chills, rigors and pain in the right hypochondrium. Eighty percent of the ALA cases showed hepatomegaly. All patients responded to treatment with metronidazole.